CHOP/GADD153 is a mediator of apoptotic death in substantia nigra dopamine neurons in an in vivo neurotoxin model of parkinsonism - Silva, Robert M.; Ries, Vincent; Oo, Tinmarla Frances; Yarygina, Olga; Jackson‐Lewis, Vernice; Ryu, Elizabeth J.; Lu, Phoebe D.; Marciniak, Stefan M.; Ron, David; Przedborski, Serge; Kholodilov, Nikolai; Greene, Lloyd A.; et al. (Journal of neurochemistry, 2005)
There is increasing evidence that neuron death in neurodegenerative diseases, such as Parkinson's disease, is due to the activation of programmed cell death. However, the upstream mediators of cell death remain largely unknown. One approach to the identification of upstream mediators is to perform gene expression analysis in disease models. Such analyses, performed in tissue culture models induced by neurotoxins, have identified up‐regulation of CHOP/GADD153, a transcription factor implicated in apoptosis due to endoplasmic reticulum stress or oxidative injury. To evaluate the disease‐related significance of these findings, we have examined the expression of CHOP/GADD153 in neurotoxin models of parkinsonism in living animals. Nuclear expression of CHOP protein is observed in developmental and adult models of dopamine neuron death induced by intrastriatal injection of 6‐hydroxydopamine (6OHDA) and in models induced by 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP). CHOP is a mediator of neuron death in the adult 60HDA model because a null mutation results in a reduction in apoptosis. In the chronic MPTP model, however, while CHOP is robustly expressed, the null mutation does not protect from the loss of neurons. We conclude that the role of CHOP depends on the nature of the toxic stimulus. For 6OHDA, an oxidative metabolite of dopamine, it is a mediator of apoptotic death.